2019
DOI: 10.1002/ppul.24299
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations and deletions in cystic fibrosis in a tertiary cystic fibrosis center in Istanbul

Abstract: Background Cystic fibrosis (CF) genotyping has garnered increased attention since the discovery of the cystic fibrosis transmembrane conductance regulator (CFTR) gene in 1989 led to the identification of over 1700 mutations on chromosome 7. Yet, little is known about the genetic profile of CF patients in Turkey. This study sought to determine the mutation distribution among CF patients seeking care at Marmara University. Methods Two hundred fifty previously diagnosed CF patients were included in the study. CFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…In a recent study from another center in Turkey whose data were not included in our national registry, CFTR mutation analysis from 250 patients with CF revealed that at least two mutations were identified in 87.6%, only one mutation was detected in 7.6%, and no mutations were identified in 4.8% of patients. Their most common mutation was F508del at 28.4%, similar to our registry, followed by 1677delTA at 6.4% . Another center in Turkey demonstrated that their overall allele informativity increased from 11.7% to 38.2% after whole‐exon sequencing of CFTR in their 17 patients with CF in whom no mutations were identified using common mutation analysis…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In a recent study from another center in Turkey whose data were not included in our national registry, CFTR mutation analysis from 250 patients with CF revealed that at least two mutations were identified in 87.6%, only one mutation was detected in 7.6%, and no mutations were identified in 4.8% of patients. Their most common mutation was F508del at 28.4%, similar to our registry, followed by 1677delTA at 6.4% . Another center in Turkey demonstrated that their overall allele informativity increased from 11.7% to 38.2% after whole‐exon sequencing of CFTR in their 17 patients with CF in whom no mutations were identified using common mutation analysis…”
Section: Discussionsupporting
confidence: 79%
“…Their most common mutation was F508del at 28.4%, similar to our registry, followed by 1677delTA at 6.4%. 21 Another center in Turkey demonstrated that their overall allele informativity increased from 11.7% to 38.2% after whole-exon sequencing of CFTR in their 17 patients with CF in whom no mutations were identified using common mutation analysis. 22 When we compare the median z-score for height, weight, and BMI of our patients with the 2017 ECFSPR annual report, it is obvious that all these parameters are much lower than in all other European countries.…”
Section: Meconium Ileus Is Often the Earliest Clinical Manifestation mentioning
confidence: 99%
“…The high population frequency of W1282X mutation was found in Turkic-speaking North Caucasus groups (Karachay and Nogais, 0.0092 and 0.0132), in Abaza (0.0039) and in Ossetians (0.0032). The 1677delTA mutation was previously found to be common in populations neighboring or with historic links to the greater Black Sea region (e.g., Bulgaria, Romania, Greece, Cyprus, and Turkey [ Estivill et al, 1997 ; Bobadilla et al, 2002 ; Atag et al, 2019 ; Petrova G. et al, 2019 ; World Health Organization [WHO], 2021 )], including Northern Iran and Georgia ( Ivashchenko and Baranov, 2002 ). We found the high population frequencies of 1677delTA variant in such autochthonous populations of the North Caucasus as Abkhazian-Adyghe [Abaza (0.0171) and Circassians (0.0098)] and Nakh [Chechens (0.0150)] groups, but not in Ossetians and Nogais ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In CF patients the most common mutations are F508del (66.8%), G542X (2.6%), N1303K (1.6%), G551D (1.5%), W1282X (1.0%), 1717-1G → A (0.83%), R553X (0.75%), 621 + 1G → T (0.54%), and R1162X (0.51%) ( Estivill et al, 1997 ; World Health Organization [WHO], 2021 ). There is a decreasing proportion of CF patients with F508del from northwestern to southeastern Europe ( Lucotte and Hazout, 1995 ; Bobadilla et al, 2002 ; Atag et al, 2019 ; Farrell et al, 2018 ), the highest frequency in Denmark (87.2%) and the lowest in Algeria (26.3%). Mutation G542X is common in the Mediterranean countries (6.1%).…”
Section: Introductionmentioning
confidence: 99%
“…The mean FEV 1 predicted value of the patients is 80.7%. 8 Respiratory samples for culture (sputum, deep pharyngeal swab [DPS], bronchoalveolar lavage [BAL], deep tracheal aspiration [DTA], endotracheal aspiration [ETA], and nasopharyngeal aspiration [NPA]) were taken from patients monthly on routine visits and in case of acute exacerbations. The preferred sample type is sputum, but it could be challenging to obtain from small children.…”
Section: Methodsmentioning
confidence: 99%